2008
DOI: 10.1016/j.tics.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated and intrinsic models of time perception

Abstract: Two general frameworks have been articulated to describe how the passage of time is perceived. One emphasizes that the judgment of the duration of a stimulus depends on the operation of dedicated neural mechanisms specialized for representing the temporal relationships between events. Alternatively, the representation of duration could be ubiquitous, arising from the intrinsic dynamics of nondedicated neural mechanisms. In such models, duration might be encoded directly through the amount of activation of sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
479
5
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(513 citation statements)
references
References 72 publications
27
479
5
2
Order By: Relevance
“…Recently, there has been a renewed interest in studying this temporal aspect of our behavior and the way in which our brain encodes this information. This has resulted in several different types of models on duration encoding that each propose different mechanisms for the encoding of duration (Gibbon, 1977;Ivry & Schlerf, 2008;Jones & Boltz, 1989;Karmarkar & Buonomano, 2007;Matell & Meck, 2004;Van Wassenhove, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a renewed interest in studying this temporal aspect of our behavior and the way in which our brain encodes this information. This has resulted in several different types of models on duration encoding that each propose different mechanisms for the encoding of duration (Gibbon, 1977;Ivry & Schlerf, 2008;Jones & Boltz, 1989;Karmarkar & Buonomano, 2007;Matell & Meck, 2004;Van Wassenhove, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, behavioral studies have shown that trial history effects and the duration after-effect do not show any selectivity to low-level visual features such as orientation (Li, Yuan, & Huang, 2015;Walker et al, 1981), arguing against a role of early visual cortex in channel based duration processing. Furthermore, many other different brain areas have been implicated in duration processing, providing alternative possible neural loci for the channel based encoding of duration (Hayashi et al, 2015;Ivry & Schlerf, 2008;Mauk & Buonomano, 2004). For example, single cell recordings in macaques have revealed duration selectivity in striatal neurons (Mello, Soares, & Paton, 2015) as well as in the pre-supplementary motor area (pre-SMA) (Merchant, Pérez, Zarco, & Gámez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While dedicated neural structures for time perception have been described (Buhusi and Meck, 2005;Coull et al, 2004;Harrington et al, 1998;Ivry and Schlerf, 2008;Morillon et al, 2009;Treisman et al, 1990;van Wassenhove, 2009;Wittmann, 2009Wittmann, , 2013, the encoding of sensory event timing has been proposed to result from the intrinsic dynamics of neural populations not necessarily dedicated to temporal processing (Johnston and Nishida, 2001;Karmarkar and Buonomano, 2007;van Wassenhove, 2009). For instance, the timing of a colored visual patch could be encoded in the dynamics of the neural population dedicated to the analysis of color (Karmarkar and Buonomano, 2007;Moutoussis and Zeki, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is an ongoing debate whether the human time-keeping system might consist of a single pacemaker-accumulator mechanisms or whether multiple pacemakers and accumulators might exist that are used depending on the tasks at hand (see Grondin, 2010, for example). For different time scales, for example, such as milliseconds, seconds to hours, or circadian cycles, previous research suggests that several internal clocks exist that differ from each other in their timekeeping properties (see Buhusi & Meck, 2009;Ivry & Schlerf, 2008). Whether even more specialized time-keeping mechanisms such as modality specific mechanisms, for example, exist is still under debate (e.g., Gamache & Grondin, 2010;Ulrich, Nitschke, & Rammsayer, 2006).…”
Section: Introductionmentioning
confidence: 99%